Multifunctional theranostic nanomedicines for cancer treatment: Recent progress and challenges - Laxmanan Karthikeyan; Shankar Sobhana; Vellingiri Yasothamani; Karunanidhi Gowsalya; Raju Vivek (Biomedical Engineering Advances, 2023)
This review intends to provide the essentially manufacturing of various types of nanomedicines utilized for the treatment of different cancers. Nanomedicine is an advanced field of research in medicine combined with nanomaterials, which is the very fastest growing branch in medicine. Especially, the development of new multifunctional theranostic nanomedicines used for the various therapeutic biomedical applications to cure several diseases including cancer. Importantly, the unique physicochemical properties of the nanomedicines provide multitasking advantages and their greater counterpart. In this review, we discussed the most important types of multifunctional theranostic nanomedicines used for the nanodrug delivery system (NDDS), photothermal therapy (PTT), photodynamic therapy (PDT), dual modal therapy (DMT), trimodal therapy (TMT) and multimodal therapy (MMT). For the progress of cancer therapy, this review focuses especially on the different types of cancer theranostic nanomedicines.